2004
DOI: 10.1002/ca.10191
|View full text |Cite
|
Sign up to set email alerts
|

Fossa navicularis: Anatomic variation at the skull base

Abstract: The fossa navicularis is a relatively rare anatomic variation of the skull base. Awareness of its existence will avoid misinterpretations of radiological images and unnecessary investigations. This study describes the appearance of the fossa navicularis, and investigates its incidence and whether it is related to pathology at the basiocciput. We studied 492 dry human skulls and 525 computer tomography (CT) images of patients. Dry skulls showing a fossa navicularis were investigated by CT scan, whereas patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 14 publications
0
35
2
1
Order By: Relevance
“…The existence of the vascular matrix might support the former theory of the embryology but does not support a notochordal etiology for the development of the FN. In addition, several MRI studies have described the FN as being filled with lymphoid tissue of the nasopharyngeal tonsils but have made these comments without histology [2-4]. Our study showed soft tissue in the fossa but no lymphoid tissue was found within it.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…The existence of the vascular matrix might support the former theory of the embryology but does not support a notochordal etiology for the development of the FN. In addition, several MRI studies have described the FN as being filled with lymphoid tissue of the nasopharyngeal tonsils but have made these comments without histology [2-4]. Our study showed soft tissue in the fossa but no lymphoid tissue was found within it.…”
Section: Discussioncontrasting
confidence: 48%
“…Of them all, our literature review found that the FN has been used most frequently with some making distinctions between the FN and the median basal canal [2, 4-5]. According to Currarino [5], the FN is a rare anatomic variant of the basiocciput and is a subtype of the canalis basilaris medianus (CBM) [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevalence of fossa navicularis was reported by several researchers, ranging between 0.9-5.3% on DISCUSSION This is the first study that demonstrated the prevalence of fossa navicularis among cleft palate patients using a CBCT device. Prevalence of fossa navicularis was reported by several researchers, ranging between 0.9-5.3% on dried skulls [4][5][6][7] , 3% on CT images 4 and 6.6% on CBCT images3. The percentage of fossa navicularis identified in this study (28.8%), was found to be higher than the percentage reported in previous studies performed on dry skulls, CT or CBCT images of the noncleft patients.…”
Section: Resultsmentioning
confidence: 99%
“…28 But in present case the depth was much less compared to previous study. According to Cankal 7 and his associates differential diagnosis of fossa navicularis includes Rathke's pouch cyst, adenoid retention cyst, adenoid hypertrophy, Tornwaldt's cyst, mucocele of sphenoidal sinus, dermoidteratoma of posterior nasopharyngeal wall.…”
Section: Discussionmentioning
confidence: 99%